Detection of haemoparasites in Japanese quail (Cortunix cortunix japonica) - Azmi, Nur Shuhada Shareen; Mohd Noor, Mohd Hezmee; Idris, Lokman Hakim; N. M. M., Isa (Faculty of Veterinary Medicine, Universiti Putra Malaysia, 2018)
Quails are known for its small size and unique qualities of low feed requirements, rapid growth, short gestation, making it an alternative for cheap source of protein other than chickens. However, there is limitation regarding the study of disease in quail production in Malaysia. In the present study, it focuses on detection of haemoparasites in Japanese quails (Cortunix coturnix japonica). Total of 30 quails were taken from different housing, consisting of 25 to 35 days of age. A thorough physical examination was done but all quails do not exhibit any typical signs such as emaciation, loss of appetite, listlessness, difficulty in breathing, and weakness. Blood sample collected for thin blood smear stained revealed that, both houses demonstrated the presence of Plasmodium sp. and Leucocytozoon sp. The results were as follows; high detection of Plasmodium sp. was noted;93.3% in house A and 100.0% in house B and low detection of Leucocytozoon sp.; 40.0% in house A and 46.7% in house B. Post-mortem examination shows no significant changes. In conclusion, there is presence of haemoparasites but absent of clinical signs and significant changes in the organs of affected quails. The current report will improve the understanding on effect of haemoparasites among quails.